PHYTOCHEMICAL PROFILE, ANTIOXIDANT AND CYTOTOXIC ACTIVITIES OF LEAF EXTRACT OF Dipteryx lacunifera DUCKE - Krislany A. L. Guedes Araujo; Herbert G. Sousa; João P. da Silva Gomes; Renato Pinto de Sousa; Éverton L. de França Ferreira; Monica T. Pupo; Pedro M. da Silva Costa; Claudia Pessoa; Mahendra Rai; Mariana H. Chaves; Gerardo Magela Vieira Junior (Química Nova)
The Dipteryx genus, a member of the Fabaceae family with approximately 14 species, is found in Brazil’s Amazon Rainforest, Northeast and Central regions, and Central America. Plants of this genus are used in popular medicine and contain coumarins, flavonoids, terpenoids, and fatty acids. Dipteryx lacunifera Ducke, known as “garampara” or “fava de morcego”, occurs in Brazil’s central-north region and has economic and energy value, along with antioxidant properties. For this study, ethyl acetate and ethylic ether soluble fraction of ethanol extract were subjected to chromatographic analysis leading to the isolation of two flavonoids, vitexin (1) and isoquercetin (6). In addition, analysis by electrospray ionization-ion trap mass spectrometry (ESI(-)-ITMS) and ultra-performance liquid chromatography coupled with electrospray ionization quadrupole-time-of-flight mass spectrometry (UPLC-ESI-QTOF-MS/MS) annotated twenty-one compounds (1-21), with seventeen of these being reported for the first time in D. lacunifera. Molecular network (GNPS) analysis grouped compounds (7-21) into flavonoids-O-glucoside, flavononol-O-glucoside, flavone-C-glucoside, proanthocyanidin, flavonol, and flavonoid-O-methoxylated classes. The FEtOAc fraction demonstrated potential antioxidant activity (half maximal effective concentration (EC50) 39.50 ± 6.51 mg mL−1), suggesting it as a promising source of antioxidants. However, neither fraction exhibited inhibition of tumor cell lines tested. These findings enhance our understanding of the chemical and biological potential of the D. lacunifera species.